Forestry for sustainable development: making it happen - Gregersen, Hans; Lundren, A.; Byron, R.N. (1998)
Sustainable development is a process of meeting the continuing, evolving needs of people while protecting and enhancing the resource base on which all production of goods and environmental services depends. Good forest management is an essential part of the sustainable development process. Given the need to share the benefits from forests, and given the uncertainty adaptive management approach is needed, one that lets us most easily adapt if we find in the future that we are on a path of sustainable development.